Designing Ethics Education for Secondary Students: A Comparative Study between Indonesia and China - Aminulloh; Rastitiati, Ni Kade Juli; Yanyan, Bi; Jiaxin, Liu; Ramendra, Dewa Putu (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study examines how ethics education for secondary students is designed and implemented across contrasting socio-cultural and policy contexts and develops a context-sensitive yet transferable design model through a comparative analysis of Indonesia and China. Addressing the limited cross-national research on ethics education design, the study employs a qualitative comparative case study involving four secondary schools in East Java and Bali (Indonesia) and Qingdao and Chongqing (China). Data were collected through online in-depth interviews with principals and teachers, virtual classroom observations, and analyses of curriculum and policy documents. The data were analyzed thematically and across cases to identify convergences and divergences in principles, pedagogical practices, and institutional orientations. The findings indicate that ethics education in Indonesia is primarily grounded in religious values and local wisdom traditions that emphasize moral character, communal harmony, and spiritual responsibility, whereas in China it is structured within civic–moral education frameworks closely aligned with national policies, highlighting discipline, social order, and collective responsibility. Despite these differing normative foundations, both systems demonstrate pedagogical convergence through dialogic learning, reflective discussions, and experiential approaches, such as life-based and project-based activities, which foster students’ empathy, social responsibility, and self-discipline. The novelty of this study lies in the development of an integrative ethics education design model that bridges religiously grounded and state-driven moral frameworks while remaining adaptable across contexts. The study contributes theoretically by conceptualizing ethics education as a design-oriented process that connects local moral grounding, reflexive pedagogy, and cross-boundary learning experiences. Practically, it offers actionable guidance for policymakers, curriculum designers, and teachers seeking culturally responsive yet globally relevant approaches to ethics education.